2018
DOI: 10.1007/s13730-018-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatic splenic rupture in a peritoneal dialysis patient

Abstract: Splenic hemorrhage is a potentially life-threatening complication usually occurring after blunt trauma to the abdomen. Atraumatic splenic rupture (ASR) is an uncommon condition, and mostly results from pathology affecting the spleen, such as tumor infiltration or infection. Here, we report a case of atraumatic rupture of a normal spleen in a patient undergoing peritoneal dialysis, and review similar cases in the literature. The case involved a 58-year-old man with nephrotic syndrome who had been undergoing per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Apresenta etiologia multifatorial, sendo a causa infecciosa viral já bem estabelecida. [1] O caso relatado apresenta paciente com infecção viral por SARS-COV2, que evolui com esplenomegalia, distúrbio de coagulação e necessidade de ECMO e diálise peritoneal. Cursou com ruptura esplênica e necessidade de esplenectomia.…”
Section: Discussionunclassified
“…Apresenta etiologia multifatorial, sendo a causa infecciosa viral já bem estabelecida. [1] O caso relatado apresenta paciente com infecção viral por SARS-COV2, que evolui com esplenomegalia, distúrbio de coagulação e necessidade de ECMO e diálise peritoneal. Cursou com ruptura esplênica e necessidade de esplenectomia.…”
Section: Discussionunclassified
“…We reviewed the relevant literature on PubMed for secondary peritonitis in PD patients since 2017 (Table 1). [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Out of the 16 cases, perforation was the most common cause of secondary peritonitis, which might be easier to diagnose due to changes in dialysate properties. Two cases were complicated with abscesses in the kidney 8 and the spleen, as shown in our case, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There were some cases of atraumatic damage of the intraabdominal organ, such as spleen rupture, bowel erosion, and perforation. Retrospective studies of the serial changes of CT peritoneography in patients with symptomatic ultrafiltration failure have shown that retroperitoneal leakage, anterior abdominal wall leakage, and inguinal hernia can occur without trauma [12][13][14] . Intra-abdominal pressure in patients on PD can be changed depending on the patients' position, dialysate volume, and coughing.…”
Section: Discussionmentioning
confidence: 99%